Penguatan Pendidikan Karakter Melalui Literasi Digital Dalam Pembelajaran Agama Islam Di Era 4.0 - Juliadi; Suprapto; Abdul Malik (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2025)
The aim of this research is to explore strengthening character education through digital literacy in Islamic Religious Education (PAI) learning in the Industrial Revolution 4.0 era. This research uses a qualitative approach with a literature study method, analyzing various sources related to the integration of technology in education, as well as the role of digital literacy in shaping student character. The research results show that digital literacy has a very important role in improving the quality of PAI learning, by giving students the ability to access, understand and manage information critically and ethically. Digital literacy also enables the development of effective communication skills and improves interactions between teachers and students in a wider context. Apart from that, digital literacy-based PAI learning can enrich teaching materials, encourage active participation of students, and help them apply Islamic religious values ​​in everyday life. Thus, strengthening character education through digital literacy can create a generation that is not only technologically savvy, but also has integrity, tolerance and a positive attitude towards differences. This research recommends curriculum development and teacher training to utilize digital literacy in PAI learning more optimally, in order to prepare students to face global challenges in the digital era.